The impact of inflation and interest rates on global stock markets: The moderating role of consumer confidence across five continents - A'la, Ahmad Zidni Nuuron; Sucipto, Agus; Yuliana, Indah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2024)
This study examines the impact of inflation and interest rates on global stock market index performance, with the moderating role of the Consumer Confidence Index (CCI) across five countries representing different continents: the United States, the United Kingdom, China, South Africa, and Australia. These countries were selected for their distinct economic policies and significant contributions to the global economy. Using the Moderated Regression Analysis (MRA) method and 2,400 monthly data observations spanning 2014 to 2023, sourced from official institutions such as central banks and financial agencies, this research provides key insights. The findings reveal that inflation positively influences index performance in the United States, the United Kingdom, and Australia, while it negatively impacts performance in China. Interest rates predominantly have a negative effect on index performance, except in the United Kingdom and China, where the effect is statistically insignificant. The moderation effect of the CCI varies by country, highlighting the role of unique economic contexts in shaping the relationship between inflation, interest rates, and stock market indices. This study offers valuable implications for policymakers in managing inflation and bolstering consumer confidence and provides strategic insights for investors navigating global economic dynamics.